Încercare de diagnoză a modernității - Czobor, Mihaela (Calitatea Vieții, 1994)
The essay ”An Attempt of Diagnosis of Modernity" is an interesting, ”critical radiography" of the modern world condition. The author combines in an original way some ideas taken from some famous authors but equally keeping her own ideas on the postmodern society.